Sekuritisasi Pandemi COVID-19 dan Tatanan Neoliberal: Menuju Deliberalisasi Ekonomi Global? - Habibah, Yasmin Nur; Pratama, Januar Aditya; Alam, Teduh Gentar (Jurnal Hubungan Internasional, 2021)
This paper is aimed to find the potential trends of the protectionism of countries and their independence on global economic chains in the midst of the COVID-19 outbreak. Securitization is a state action to increase the status of an issue into an existential threat. In accordance with the theory of securitization, since the spread of COVID-19 becomes a pandemic and threatens health security of the people, countries take part in securitization actions through the application of rules on limiting medical industry transactions, whose products are urgently needed by other countries together with the securitization of the COVID-19 pandemic issues. Thus, the authors examine the acts of securitization from case studies of three countries: Britain, France, and the United States, as samples from countries supporting neoliberal order who has done this action. So, it is known that during the pandemic, countries in the world failed to maintain their liberal economic practices. Then, weaknesses are found in the global liberal economic system, where the dependency of the production and distribution chains on one another can lead to vulnerability to unilateral termination by several involved countries which prioritize their national interests and re-implement economic nationalism.